Predictive model for the risk of paediatric intensive care utilization in children with medical complexity: a longitudinal retrospective cohort study - Pérez-Ardanaz, Bibiana; Gutiérrez-Rodríguez, Laura del Carmen; Gómez-González, Alberto José; Morales-Asencio, José Miguel; Montero-García, Antonio Jesús; León-Campos, Álvaro (Wiley, 2024)
BackgroundChildren with medical complexity (CMC) are at increased risk of admission in intensive care. Despite improvements in mortality rates, there remains a burden of morbidity, long-term health care needs and hospital readmissions. Beyond clinical factors, socio-demographic determinants could impact utilization of acute services.AimTo identify risk factors that can differentiate CMC who are admitted to the paediatric intensive care unit (PICU).Study DesignA 6-year longitudinal retrospective cohort study evaluated clinical, socio-demographic and health care utilization.ResultsA total of 248 CMC were included, with a median age of 13 years (9.75–17.00). Intensive care admission rate was 47.2%. The risk of PICU admission was higher for children undergoing surgical interventions (HR = 1.58, 95% CI 1.34–1.86, p < .001) and those using medical devices (HR = 1.81, 95% CI 1.54–2.13, p < .001). Mother's higher educational level was a protective factor (HR = 0.66, 95% CI 0.55–0.79, p < .001). Multivariable analysis revealed significant associations between risk of admission and the presence of malignancy, comorbidities, home medical devices, surgical procedures and higher health care utilization. Children's age and higher maternal educational level acted as protective factors.ConclusionSocio-demographic factors should be considered in the provision of care to CMC. Individualized assessments to guide supportive interventions adapted to socio-economic factors may prevent PICU admissions.Relevance to Clinical PracticeThis study highlights the importance of integrating individualized assessments of socio-demographic risk factors, such as maternal educational level, into the clinical practice of paediatric nurses. Moreover, targeted interventions, including educational resources and community support programmes, may optimize care.
Keywords: Enfermería de cuidados intensivos - Evaluación del riesgo; Children; Health resources; Multiple chronic conditions; Nursing; Paediatric critical care